دور الدستور في تعزيز التنمية المستدامة - عبدالقادر، مهند ضياء (الجامعة المستنصرية - كلية القانون, 2021)
لقد كان مؤتمر الأمم المتحدة للبيئة والتنمية المنعقد في ريو دي جانيرو عام 1992 بمثابة الحد الفاصل في الفكر السياسي والقانوني في المجتمعات البشرية المختلفة... ففكرة التنمية المستدامة التي صاغها هذا المؤتمر أصبحت الهدف الذي تسعى إلى تحقيقه الحكومات... ولأن الحكومات تستند في نشاطاتها المختلفة إلى الدستور الذي يوفر القواعد الأساسية لممارسة السلطة لمهامها المختلفة. أصبح من الواجب أن يقوم الدستور بدور بناء في سبيل تحقيق متطلبات هذه التنمية. ويتحدث بحثنا الموسوم (دور الدستور في تعزيز التنمية المستدامة) عن مجموعة القواعد والأحكام الدستورية التي يمكن لها تحقيق متطلبات التنمية... وتحقيق ذلك يحتاج ابتداء إعادة صياغة القواعد المنظمة للسلطة باعتبارها الوسيلة الأنجح لتحقيق التنمية... إضافة إلى إعادة صياغة النصوص المنظمة للحقوق والحريات العامة لتواكب التطورات الحاصلة في حقوق الإنسان وانتقالها من جيل لأخر. The role of the constitution in promoting the sustainable development. The United Nations conference on environment and development (UNCED) held in rio de janiero in 1992, was the dividing line of political and legal thought in different societies. The idea of sustainable development formulated by this conference has become the goal pursued by the governments, and now the governments depend are based on their various activities to the constitution, which provides the basic rules for exercise of power of their various tasks. The constitution must play a constructive role in order to meet the requirements of this development. Our research deals with the set of rules and constitutional provisions that can fulfill the requirements of development… Achieving this requires the re-formulation of the rules governing the authority as the most effective means of achieving development. In addition to reformulating the texts of the organization of right and public freedoms to keep pace with developments in human right and their transition from generation for another.
Keywords: حقوق الإنسان -- التنمية المستدامة -- الدساتير العراقية -- النصوص القانونية